Pengaruh sistem pemesanan makanan digital terhadap ketepatan waktu pemberian makanan dan kepuasan pasien - Lina Ferryana; Dida Akhmad Gurnida; Siska Wiramihardja (Jurnal Gizi Klinik Indonesia, 2022)
Effect of digital food ordering system on timeliness of feeding and patient satisfactionBackground: Computer-based information systems simplify food ordering, speed up the calculation of order data, and reduce operational costs for patient food ordering processes to reduce the time lag between ordering food and serving it to consumers. Only a few studies have examined the effect of digital food ordering applications on feeding accuracy and patient satisfaction.Objective: This study aims to determine the relationship between the digital food ordering system and the timeliness of feeding, and the relationship between timeliness of feeding, taste, menu variety, staff appearance, and food service with patient satisfaction.Methods: This study uses a mixed design design with a parallel concurrent mixed method. Quantitative research uses the one-group pretest-posttest pre-experimental design without a control group design and qualitative research uses the social constructivism–interpretation paradigm. The research was conducted in July 2022 at the Bayu Asih Hospital in Purwakarta. The study population consisted of 91 inpatients using a sampling technique, namely total sampling, while the number of samples for qualitative data was five persons using purposive sampling. Bivariate analysis used the Wilcoxon and Chi-Square tests, while the qualitative analysis used a deductive approach.Results: The average time for serving food with manual ordering tends to be greater, namely 181.5 seconds, which decreases to 156.62 seconds after using a digital food ordering system. Most of patients (73.6%) were satisfied with the timeliness of feeding, the taste of the food provided, the varied menu, and the neat appearance of the servers. The results of the analysis showed a significant relationship between the timeliness of food serving (p=0.006); food taste (p=0.001); menu variety (p=0.001); and the appearance of the waitress (p=0.001) with patient satisfaction.Conclusion: The timeliness of feeding increases after using a digital food ordering system. Timeliness of feeding, food taste, variety of food menus, appearance of food serving staff, and food service are significantly related to patient satisfaction.